Effect of reduced glutathione on the indexes of oxidative stress and heme metabolism in liver and blood of rats under hemin chloride injection in vivo - Nikitchenko, I.; Pavliy, A.; Barannik, T.; Gevoian, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Heme (iron-protoporphyrin IX) is involved in various cellular functions. The release of heme under hemolysis or under the damage of intracellular hemeproteins leads to its accumulation in tissues and, as a result, to the activation of free radical processes. Reduced glutathione (GSH) functions as an endogenous water-soluble antioxidant and a regulator of cells redox status, but its effect on the development of oxidative stress under hemin action in mammals remains not investigated. The aim of this work was to study the effect of hemin chloride on some hemeproteins activity and a number of prooxidant-antioxidant status indexes in rat liver and blood under GSH level modulation in vivo. White male rats weighing 170–280 g were taken for investigation. Hemin chloride and GSH were injected intraperitoneally. Blood plasma, homogenate, and postmitochondrial fraction of liver were the objects of study. Hemin chloride injection (50 mg/kg body weight) caused the increase in heme-containing products level in blood and free heme level in liver of rats, which was accompanied by the activation of free radical processes in these tissues. The accumulation of free heme in liver was proved by an increase in tryptophan 2,3-dioxygenase (TDO) holoenzyme activity and heme saturation. The pretreatment by GSH (500 mg/kg body weight) 0.5 h before hemin chloride injection normalized GSH content, but did not prevent heme accumulation, the decrease in triglycerides level and the increase in lipid hydroperoxides content in rat blood plasma under hemin action. In liver, GSH injection prevented the increase in lipid hydroperoxides and protein carbonyl derivatives concentration as well as in TDO holoenzyme activity, and decreased the degree of TDO heme saturation. All these changes occurred under GSH content increase in liver. Catalase activity in liver did not differ from the control values after hemin chloride injection as well as after glutathione and hemin coadministration. The analysis of relationship between parameters studied in this work revealed the strong positive correlation between GSH content in plasma and liver (r=0.85; p<0.001), which was consistent with literature data on the significant role of liver in supplying other tissues with reduced glutathione. A negative correlation was found between lipid peroxidation products and triglycerides content in plasma (r=–0.52; p<0.05), which indicated the participation of triglycerides unsaturated fatty acids as substrates in the peroxidation processes under hemin action. No significant correlation between GSH and hydroperoxides content, as well as between GSH and heme-containing products levels in blood plasma was revealed. Thus, the water-soluble antioxidant glutathione was not effective enough to prevent damage of lipid components in blood under hemin chloride action in the selected dose. In the liver, on the contrary, GSH injection prevented heme accumulation and oxidative stress development under hemin action, which was obviously associated with an increase in the GSH content in this organ.